2007
DOI: 10.1074/jbc.m611833200
|View full text |Cite
|
Sign up to set email alerts
|

The 1.8 Å Crystal Structure of PA2412, an MbtH-like Protein from the Pyoverdine Cluster of Pseudomonas aeruginosa

Abstract: Many bacteria use nonribosomal peptide synthetase (NRPS) proteins to produce peptide antibiotics and siderophores. The catalytic domains of the NRPS proteins are usually linked in large multidomain proteins. Often, additional proteins are coexpressed with NRPS proteins that modify the NRPS peptide products, ensure the availability of substrate building blocks, or play a role in the import or export of the NRPS product. Many NRPS clusters include a small protein of ϳ80 amino acids with homology to the MbtH prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 45 publications
3
90
0
3
Order By: Relevance
“…An MbtH-like protein is found in many of the gene clusters involved in the synthesis of siderophores and peptide and aminocoumarin antibiotics. Although the requirement of MbtH-like proteins for the formation or secretion of secondary metabolites in Streptomyces (31,54) and for that of pyoverdine at wild-type levels in Pseudomonas aeruginosa (17) has been shown experimentally, the function of these proteins is still unknown, because different mbtH-like genes can functionally replace each other (31,54).…”
Section: Resultsmentioning
confidence: 99%
“…An MbtH-like protein is found in many of the gene clusters involved in the synthesis of siderophores and peptide and aminocoumarin antibiotics. Although the requirement of MbtH-like proteins for the formation or secretion of secondary metabolites in Streptomyces (31,54) and for that of pyoverdine at wild-type levels in Pseudomonas aeruginosa (17) has been shown experimentally, the function of these proteins is still unknown, because different mbtH-like genes can functionally replace each other (31,54).…”
Section: Resultsmentioning
confidence: 99%
“…The iupU gene (nucleotides [nt] 2506417 to 2533221), encoding a protein of 960.3 kDa containing seven NRPS modules, is located 28 kb upstream of iupABC, encoding a siderophore uptake system (29). The close proximity to iupABC and the linkage with mbtH, a gene required for production or secretion of siderophores and frequently clustered with siderophore biosynthesis genes (11,47), indicated that the iupU gene could be involved in siderophore biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Drake et al (5) solved the crystal structure of an MbtH-like protein from Pseudomonas aeruginosa. The protein displays a new protein fold and is shaped like a thin arrowhead, with the point of the arrow formed by the C-terminal ␣-helix.…”
Section: Discussionmentioning
confidence: 99%
“…in catalysis, regulation, transport, or protein-protein interactions. The three-dimensional structures of two MbtH-like proteins have been experimentally determined (4,5), but again this did not allow their function to be determined. The first biochemical evidence for the function of MbtH-like proteins in non-ribosomal peptide biosynthesis has been recently provided in two rapid reports by Felnagle et al (6) and Zhang et al (7).…”
mentioning
confidence: 99%